PKM PENINGKATAN PRODUKSI OLAHAN KANGKUNG SEBAGAI JAJANAN SEHAT DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Syafriani Syafriani; Afiah Afiah; Nia Aprila (Universitas Pahlawan Tuanku Tambusai, 2022)
Kangkung land (Ipomea reptans Poir) is one of the horticultural plants that are very popular with the people of Indonesia because of its savory taste. This plant belongs to the group of seasonal crops and is short-lived and does not require large areas to cultivate it so that it is possible to cultivate it in cities where land is generally limited. In addition to the savory taste, the nutrients contained in kale vegetables are quite high. Kale production in Indonesia can reach 10?646.00 tons in 2021 (BPS 2021). The marketing opportunities for land kale are getting wider to supermarkets with the entry of kale vegetables to supermarkets will increase the selling price of this vegetable (Taufik, 2012). This water spinach plant (Ipomoea reptans) is only sold in the market and processed into vegetables, even though there are many processed products that can be used as healthy snacks from this kale raw material. Kangkung is one of the most popular vegetables in Indonesia. This plant comes from the tropics, especially Africa and Asia. Kangkung contains nutrients such as protein, fat, carbohydrates, calcium, phosphorus, iron, sodium, potassium, vitamin A, vitamin B, and vitamin C. (Priyowidodo, 2012). The purpose of this activity is to explore innovative ideas, increase creativity, instill an entrepreneurial spirit, train mentally and teach to work hard and be responsible. In addition, another goal is to reduce the waste generated by processing it into kale chips, kale sticks, and kale nuggets. There are several obstacles faced, namely (1) Limited capital. (2) Low motivation for entrepreneurs with kale as the main ingredient. (3) There is no diversity of processed kale products. (4) The absence of packaging and marketing of kale. Keywords:steak, nuggets, kangkong chips